Multicultural special education for inclusive classrooms intersectional teaching and learning - Perzigian, Aaron B. T.; Aziz, Nahrin (New York, NY Routledge, Taylor & Francis Group, 2023)
"This book provides a comprehensive exploration of critical topics in multicultural special education. Filled with case studies, objectives, and summaries to support deeper learning, chapters discuss privilege and power in K-12 school systems, effective and differentiated instruction, culturally competent IEPs and transition plans, and appropriate assessment. Drawing from seminal multicultural education and culturally sustaining pedagogies, this essential text helps educators develop the skills necessary to affirm and honor identities while meeting the instructional needs of culturally diverse students with disabilities"--
Social construction of disability / Lindsay Foreman-Murray -- Intersection of multicultural education and special education in theory and practice / Kevin Roxas and Francisco Rios -- Alternative education placements for students with disabilities / Kemal Afacan and Kimber L. Wilkerson -- Culturally responsive positive behavioral interventions and supports for all youth : practitioner framework and introduction to learning lab / Dian Mawene, Aydin Bal, Sophia C.F. Dodge, and Morgan Mayer-Jochimsen -- Cultural competence in special education assessment / Veronica Kang and Sunyoung Kim -- Cultural competence in special education instruction / Min-Chi Yan, Sunyoung Kim, and Veronica Kang -- Affirming IEP and transition plans for students with disabilities / Min-Chi Yan and Brandi Walton -- Family, school, and community / Shane Smith and Shawn Savage -- Engaging native families and tribal communities in children's education : venerating indigenous knowledges as the fundamental principles on which to base pedagogy and practice / Nahrin Aziz -- School-community partnerships for a multicultural education / Ario Salazar.
Includes bibliographical references and index.
Keywords: Culturally relevant pedagogy -- United States; Multicultural education -- United States; Children with disabilities -- Education -- United States; Inclusive education -- Social aspects -- United States; Special education -- Social aspects -- United States